Pengaruh Citra Merek, Promosi, dan Fasilitas terhadap Kepuasan Konsumen di Ayam Khas Nusantara Suzuya Marelan - Mhd. Rizky Sitorus; Hendry Hendry; Rizki Samuel Timoti Lbn. T.; Timothy Reinhard Mangarahon T. B.; Felita Paramita; Fhenny Adriana Siregar (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2026)
The following study aims to analyze the influence of brand image, promotion, and facilities on customer satisfaction at Ayam Khas Nusantara Suzuya Marelan. The research was motivated by fluctuations in customer numbers, indicating suboptimal levels of customer satisfaction. Factors suspected of influencing this situation include poor brand image reinforcement, suboptimal promotional strategies, and restaurant facilities that do not fully meet customer needs.The study used a quantitative approach, and data collection was conducted through the distribution of questionnaires to Ayam Khas Nusantara Suzuya Marelan customers. Data analysis used statistical methods to understand the impact of each variable on customer satisfaction. The study findings indicate that brand image, promotion, and facilities have a positive and significant impact on customer satisfaction, both individually and in combination. Among these variables, facilities emerged as the most dominant element influencing customer satisfaction.